Kandungan Gula dan Vitamin C pada Minuman Ready to Drink dengan Klaim Vitamin C - Hidayati, Rima (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2024)
Declining COVID-19 positive case does not reduce food industry, especially ready to drink (RTD) beverages industry, to sell product with vitamin C claim. Furthermore, increasing air pollution and climate change has encouraged consumers to maintain their immune system. Meanwhile, RTD beverages are well known as calorie drink with its high sugar content, hence could increase risk of type 2 diabetes. This research aims to evaluate sugar type, sweetener type, sugar and vitamin C content, and vitamin C claim which stated on the label of vitamin C claimed RTD beverages (food category 14.1.4.1 and 14.1.4.2) that is sold in various minimarket and supermarket in Bogor area, and online shop during February to May 2023. Total sugar content subsequently compared to front of pack (FoP) labelling guidance from United Kingdom (UK), Singapore, and Indonesia. This research has collected 70 samples, that consists of fruit juice drink, fruit flavored drink, fruit drink, tea drink, jelly drink, carbonated flavored drink, and milk flavored drink. As much as 74.28% among the samples contained sugar, mainly from sucrose, above 6 g/100 mL. Besides sugar, 52.74% samples contained sweetener, with stevia as natural sweetener more used than artificial sweetener. Based on sugar FoP labelling guidance, the majority of samples was in medium (amber) category in UK, C (orange) category in Singapore, and orange category in Indonesia. Source of vitamin C was the most claim stated as nutritional content claim, while vitamin C function claim to help collagen formation and maintenance was more mentioned compared to immunity claim.